(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The patterns, trends, and effects of cybercrimes on the financial sector are the subject of this research. A thorough understanding of the nature and effects of financial cybercrimes is necessary since these crimes constitute serious dangers to people, companies, and governments. Cybersecurity experts, lawmakers, and law enforcement can better protect financial systems, organisations, and people from cyberattacks if they study the methods hackers use to compromise these systems. Significant monetary losses, diminished faith in online transactions, and interruptions to essential infrastructure and services are some of the far-reaching effects of financial cybercrimes on the economy. Beyond the obvious monetary losses, these effects ripple via investment choices, customer trust, and productivity. Financial cybercrimes may have a significant economic effect; stakeholders need to invest in cybersecurity, strengthen authentication mechanisms, and raise cybersecurity awareness to mitigate this. To further discourage cybercriminals and enable coordinated reactions to cybercrimes that span international borders, thorough rules and international collaboration are required. It takes a look at the many forms of cybercrime in India, the damage they do, and the steps the government and others have done to stop them. In addition to outlining possible solutions to lessen the impact of cybercrime, the paper emphasises the difficulties in doing so.